Vestibular Stimulation on a Motion-Simulator Impacts on Mood States - Winter, Lotta; Kruger, Tillmann H.; Laurens, Jean; Engler, Harald; Schedlowski, Manfred; Straumann, Dominik; Wollmer, M. A. (Frontiers in Psychology, 2012)
We are familiar with both pleasant and unpleasant psychotropic effects of movements associated with vestibular stimulation. However, there has been no attempt to scientifically explore the impact of different kinds of vestibular stimulation on mood states and biomarkers. A sample of 23 healthy volunteers were subjected to a random sequence of three different passive rotational (yaw, pitch, roll) and translational (heave, sway, surge) vestibular stimulation paradigms using a motion-simulator (hexapod). Mood states were measured by means of questionnaires and visual analogue scales. In addition, saliva cortisol and α-amylase samples were taken. Compared to a subliminal control paradigm all rotational and two translational stimulations produced significant changes in mood states: Yaw rotation was associated with feeling more comfortable, pitch rotation with feeling more alert and energetic, and roll rotation with feeling less comfortable. Heave translation was associated with feeling more alert, less relaxed, and less comfortable and surge translation with feeling more alert. Biomarkers were not affected. In conclusion, we provide first experimental evidence that passive rotational and translational movements may influence mood states on a short term basis and that the quality of these psychotropic effects may depend on the plane and axis of the respective movements.